إستراتيجيات الكلام باللغة العربية لدى المتعلمين الناجحين: دراسة وصفية بمعهد نور الهداية بولاية رياو - سارياتي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims to find out the speaking strategies in Arabic language among successful language learners of Ma'ahad Nurul Hidayah in Riau particularly the factors affecting choice of speaking strategies. The researcher chose non random sampling of respondents which is called target sampling consisting of four successful learners at the Ma'ahad. This study is a qualitative research where the researcher used descriptive approach to collect data. Two tools were applied in this study: drama and presentation of specific topic by the respondents. The researcher also observed two language tasks by each respondent and interviewed them to obtain the information that could not be found in the observation. It was found that the successful learners of Ma'ahad Nurul Hidayah used many direct strategies and indirect strategies to develop their speaking skill; they are memory strategies, cognitive strategies, metacognitive strategies, affective strategies and social strategies. They did not use compensation strategies to develop speaking skills. One of the respondents used “imagery strategy” to develop her speaking skills, yet this strategy is for listening and reading only, according to Oxford (1990). Another result of this study also indicates that some of the factors affecting choice of speaking strategies among successful language learners at the Ma'ahad include high language proficiency (grammar), conducive environment, motivation from pears or from other things around them and the level of language in the courses studied.